The little mermaid: favourite tales - Daly, Audrey; Price-Thomas, Brian Andersen, Hans Christian (Ladybird London, 1993)
This beloved fairy tale, retold for young readers, transports children to a magical underwater world. It explores themes of love, sacrifice, and the power of dreams, captivating young imaginations and sparking a love for storytelling.